Network intrusion detection - David J. Marchette (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
Attacks against computers and the internet are in the news every week. These primarily take the form of malicious code such as viruses and worms, or denial of service attacks. Less commonly reported are attacs with gain access to computers, either for the purpose of producing damage (such as defacing web sites or deleting data) or for the opportunities such as access provides to the attacker, such as accessto bank accounts or controlsystems of power stations. This chapter will discuss some of the areas in which computational statistics can be applied to these and related problems.
Keywords: 330